2023
DOI: 10.1021/acs.biomac.3c00337
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Degradation of Cellulose Acetate by Embedded Enzymes: Accelerated Enzymatic Degradation and Biodegradation under Simulated Composting Conditions

Abstract: A green strategy that significantly accelerates the biodegradation rate of cellulose acetate (CA) by triggering deacetylation was demonstrated. Lipase isolated from Candida rugosa was immobilized on CA particles (immobilized lipase (IL)) by a physical entrapment method and further incorporated in CA films. After 40 days of aging in contact with external enzymes (lipase and cellulase), the number-average molecular weight (M n) of CA/IL 5% decreased by 88%, while the M n of CA only exhibited a 48% reduction. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
(121 reference statements)
1
4
0
Order By: Relevance
“…In the case of the UV-irradiated samples, the char yield decreased for CA-7UV and increased for CA-CD-7UV. These findings are in correlation with earlier studies, where the char yield initially deceased and then increased during, e.g., enzymatic deacetylation and degradation of CA films . There were no large changes in the maximum decomposition temperatures of the different materials, which varied within the range 354–361 °C.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the case of the UV-irradiated samples, the char yield decreased for CA-7UV and increased for CA-CD-7UV. These findings are in correlation with earlier studies, where the char yield initially deceased and then increased during, e.g., enzymatic deacetylation and degradation of CA films . There were no large changes in the maximum decomposition temperatures of the different materials, which varied within the range 354–361 °C.…”
Section: Resultssupporting
confidence: 91%
“…Biodegradation of CA has been widely studied in different environments, including enzymatic degradation, simulated composting, soil and marine environments, under UV irradiation, and with catalysts to trigger the UV or biodegradation. Still the knowledge is fragmented due to the complexity of the processes with many variables and the sensitive structure–environment relationships . Furthermore, mineralization as the final stage of biodegradation was often not quantified by monitoring CO 2 emissions .…”
Section: Introductionmentioning
confidence: 99%
“…Lipases are present in a high majority of living organisms, with a large number of fungi also producing lipases . Tokiwa et al, demonstrated the ability of lipase to degrade synthetic polyesters, and Alejandra et al, confirmed lipase’s degradation capabilities in poly­(3-hydroxybutyrate- co -4-hydroxybutyrate). , Ultimately, lipase is a readily available enzyme and shown to degrade polyesters. , Figure shows that lipase induces a trend in enzymatic hydrolysis near identical to that of proteinase K. The presence of the identical catalytic triad in both lipase and proteinase K may be the cause for the similar response, with both proteinase K and lipase exhibit the ‘catalytic triad of aspartic acid (Asp), histidine (His), and serine (Ser) . The catalytic triad catalyzes the nucleophilic attack on carbonyl carbons in esters using the active site serine. , While further work exploring wider enzyme structures may yield varied biodegradation capabilities, it is still important that both hydrolases have promoted activity on UV degraded polymers irrespective of individual enzymes.…”
Section: Resultsmentioning
confidence: 97%
“…35,36 Ultimately, lipase is a readily available enzyme and shown to degrade polyesters. 37,38 Figure 5 shows that lipase induces a trend in enzymatic hydrolysis near identical to that of proteinase K. The presence of the identical catalytic triad in both lipase and proteinase K may be the cause for the similar response, with both proteinase K and lipase exhibit the 'catalytic triad of aspartic acid (Asp), histidine (His), and serine (Ser). 39 The catalytic triad catalyzes the nucleophilic attack on carbonyl carbons in esters using the active site serine.…”
Section: Trends Utilizing Other Enzymesmentioning
confidence: 99%
“…The above phenomena were attributed to the hydrolysis and breakage of the C–O–C bonds in the structure, followed by biodegradation under the synergistic action of microorganisms and enzymes. 49…”
Section: Resultsmentioning
confidence: 99%